Pengembangan Modul Aswaja: Biografi, Konsep Pemikiran dan Karya Abu Hasan Al As’ari - Asharul Muttaqin; Zainal Rosyadi; Siti Uswatun Kasanah (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
The purpose of this research is to develop the Ashlisunah wal jamaah course module, with a research focus on the development of the biographical module, the thought concepts and works of Abu Hasan As'ariyah which had not existed before. Usi1ng the Research and Development (R&D) method developed by Thiag1arajan, namely 4-D model which includes 4 steps of research and development, namely definition, design, development, and deployment. Dat1a was co1llected from the assessment of 3 exp1erts through expert validation sheets, 2 peers reviewers, 4 lecturers and 2 student classes through a student res1pondent questionnaire. 1Results 1Research shows that the mo1dule is sui1table for use as teaching material in the Aswaja course. Thi1s is b1ased on mate1rial validation 86.50 (very good), medi1a experts 85.65 (very good), linguists 95.22 (very good), lecturers 96.22 (very good) and peer reviewers 96.22 (very good).